Effect of the presence of dental plaque on oral sugar clearance and salivary pH: an in vivo study - Pradhan, Debapriya; Jain, Deepak; Gulati, Amit; Kolhe, Swapnil J; Baad, Rajendra; Rao, B Sunil (The journal of contemporary dental practice, 2012)
Fermentable carbohydrates and microorganisms in the plaque play a significant role in the pathogenesis of dental caries. Oral clearance of sugars and salivary pH is affected by the presence of plaque. This study was conducted to study the effect of the presence of plaque on the salivary clearance of sucrose and on salivary pH. The study design was of a randomized controlled parallel group clinical trial and included two groups: The control group and plaque group, as follows: Control group--subjects without plaque and plaque group--subjects with plaque. Salivary sucrose determination was done by using the anthrone technique. A digital pH meter estimated the salivary pH. The Student's t test and Mann-Whitney test was employed to compare the intergroup differences. Pearson's correlation coefficient was used for analysis. The salivary sucrose clearance time was increased by presence of plaque. The presence of plaque led to increased salivary sucrose concentrations and increased the salivary sucrose clearance time. The dental caries is the dynamic relationship among the dental plaque microbiota, dietary carbohydrates, saliva and cariogenic potential of the dental plaque. Caries occur preferentially in the dentition sites characterized by high exposure to carbohydrate and diminished salivary effect.